Hypofractionated Volumetric-Modulated Arc Radiotherapy for Patients With Non-Small-Cell Lung Cancer Not Suitable for Surgery or Conventional Chemoradiotherapy or SBRT - Shen, Junyue; Yang, Dan; Chen, Mailin; Jiang, Leilei; Dong, Xin; Li, Dongming; Yu, Rong; Yu, Huiming; Shi, Anhui (Frontiers in Oncology, 2021)
Background: Hypofractionated radiotherapy (HypoRT) has been used to pursue an alternative treatment regimen for patients with non-small-cell lung cancer (NSCLC) who are not eligible for stereotactic ablative radiotherapy (SABR), surgery or concurrent chemoradiotherapy (CCRT) and has shown good local control and safety. We analyzed the feasibility of using volumetric-modulated arc radiotherapy (VMAT) with the simultaneous integrated boost (SIB) technique to achieve high local control with few treatment-related toxicities. Patients and Methods: A total of 45 patients with stage I-IV NSCLC who were not candidates for SABR, surgery or CCRT were included in the present study. All patients received a prescribed dose of 60 to 66 Gy in 15 fractions. Local progression-free survival (LPFS), PFS, overall survival (OS), and toxicities were retrospectively analyzed. Results: Twenty-eight patients (64.4%) had stage IV or recurrent disease in this study. The median follow-up time was 8 months (0-34 months). The median OS (mOS) and PFS (mPFS) were 10 months and 16 months, with 12-month OS and PFS rates of 49.2% and 50.7%, respectively. The 12-month and 18-month LPFS rates were 87.0% and 72.5%. Patients receiving ≥ 66 Gy (n = 23) to the gross tumor volume (GTV)/internal gross target volume (IGTV) had significantly longer PFS (mPFS = 20 months) than those receiving 60 Gy (n=21) to the GTV/IGTV (mPFS = 5 months) (p = 0.027). Twenty-one (47.7%) patients had disease progression at the time of analysis. Of these, 7 (15.9%), 5 (11.4%) and 14 (31.8%) had local recurrence, locoregional failure and distant metastasis, respectively. All cases of local recurrence were found within the SIB region. One patient had grade 3 pneumonitis, and one patient had grade 3 esophagitis. No grade 4 or higher toxicity was observed. Conclusion: The 60 to 66 Gy in 15 fractions RT regimen provides favorable local control and survival with well-tolerated toxicities. Hypofractionated VMAT+SIB is an alternative treatment option for patients with NSCLC who cannot tolerate standard definitive therapy.